Does Segmentation Really Work? Effectiveness of Matched Graphic Health Warnings on Cigarette Packaging by Race, Gender and Chronic Disease Conditions on Cognitive Outcomes among Vulnerable Populations. Issue 6 (3rd June 2018) - Hayashi, Hana; Tan, Andy; Kawachi, Ichiro; Minsky, Sara; Viswanath, Kasisomayajula
Abstract : We examined the differential impact of exposure to smoking-related graphic health warnings (GHWs) on risk perceptions and intentions to quit among different audience segments characterized by gender, race/ethnic group, and presence of chronic disease condition. Specifically, we sought to test whether GHWs that portray specific groups (in terms of gender, race, and chronic disease conditions) are associated with differences in risk perception and intention to quit among smokers who match the portrayed group. We used data from Project CLEAR, which oversampled lower SES groups as well as race/ethnic minority groups living in the Greater Boston area ( n = 565). We fitted multiple linear regression models to examine the impact of exposure to different GHWs on risk perceptions and quit intentions. After controlling for age, gender, education and household income, we found that women who viewed GHWs portraying females reported increased risk perception as compared to women who viewed GHWs portraying men. However, no other interactions were found between the groups depicted in GHWs and audience characteristics. The findings suggest that audience segmentation of GHWs may have limited impact on risk perceptions and intention to quit smoking among adult smokers.